Explaining the So-Called 'Casimir Force' with Nonlinear Physics (Global Journal of Science Frontier Research, 2020)
In the article "A New Twist of the Quantum Vacuum" published in the October issue of Physics Today, 2019 (p. 74), the author Jeremy Munday [1] share the experiment he did with his research group -the results was published in 2018. They used a solid birefringent crystal of calcite, which has anisotropic optical properties. They deposited on it optically isotropic layer of aluminum oxide with thickness d = 30 nanometers or less. Then they deposited a layer of liquid crystal on top of the aluminum oxide.
Keywords: A New Twist of the Quantum Vacuum